Association of ABCB1 gene polymorphisms and their haplotypes with response to antiepileptic drugs: a systematic review and meta-analysis - Haerian, B.S.; Lim, K.S.; Tan, C.T.; Raymond, A.A.; Mohamed, Z. (2011)
Aims: Several studies demonstrated a link between ABCB1 gene variants and the response to treatment in epilepsy, but the results have been inconclusive. Here, we performed the first haplotype meta-analysis to examine the association of haplotypes of ABCB1 common variants with the response to treatment in epilepsy. Materials & methods: We meta-analyzed the studies that evaluated the role of ABCB1 C1236T, G2677T/A and C3435T polymorphisms and their haplotypes in the response to treatment. Results: Meta-analysis of 23 studies (7067 patients) showed no significant association of ABCB1 alleles, genotypes and haplotypes with the response to treatment in the overall population or in each ethnicity subgroup. Conclusion: Our data suggest that the haplotypes of these loci may not be involved in the response to treatment.